Chinatown No More Taiwan Immigrants in Contemporary New York - Chen, Hsiang-Shui (Cornell University Press, 1992)
By focusing on the social and cultural life of post-1965 Taiwan immigrants in Queens, New York, this book shifts Chinese American studies from ethnic enclaves to the diverse multiethnic neighborhoods of Flushing and Elmhurst. As Hsiang-shui Chen documents, the political dynamics of these settlements are entirely different from the traditional closed Chinese communities; the immigrants in Queens think of themselves as living in "worldtown," not in a second Chinatown. Drawing on interviews with members of a hundred households, Chen brings out telling aspects of demography, immigration experience, family life, and gender roles, and then turns to vivid, humanistic portraits of three families. Chen also describes the organizational life of the Chinese in Queens with a lively account of the power struggles and social interactions that occur within religious, sports, social service, and business groups and with the outside world.